(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In this paper we report results of faunistic studies, regarding Lepidoptera Pterophoridae, realized in central-southern and insular Italy. Remarks on 39 species are reported, of these Oxyptilus propedistans (Bigot & Picard, 1988), Oxyptilus jaeckhi (Bigot & Picard, 1991), Capperia marrubii Adamczewski, 1951, Stenoptilia grisescens Schawerda, 1933, and Stenoptilia arvernica (Peyerimhof, 1875), are new for the Italian fauna.